Optimalisasi Pendistribusian Zakat, Infak dan Sedekah Baznas Jember Dalam Upaya Meningkatkan Status Mustahik Menjadi Muzakki Di Kampung SDGs Kecamatan Bangsalsari Kabupaten Jember - Andika; Misbahul Munir (Fakultas Dakwah UIN KHAS Jember, 2022)
Zakat, infaq and alms are one source of income for Muslims in empowering the Muslim community. No wonder there are many institutions that manage zakat, infaq and alms to empower Muslims, one of which is Baznas Jember. This research focuses on three things, namely, how to optimize the distribution of zakat, infaq and alms in increasing the status of mustahik to become muzakki, how Baznas' efforts are to increase the status of mustahik to become muzakki and what are the supporting and inhibiting factors for the distribution of ZIS in increasing mustahik to muzakki in the SDGs Bangsalsari village. Jember. This study aims to determine the distribution of zakat, infaq and alms in increasing the status of mustahik to muzakki in the village of SDGs Bangsalsari Jember. This research uses a qualitative approach with the type of field research research (field research). The results of this study indicate that: 1) Optimization of the distribution of zakat, infaq and alms in an effort to increase the status of mustahik to muzakki in the village of SDGs Bangsalsari Jember, namely the distribution of consumptive zakat and productive zakat, direct and indirect distribution. 2) What are the efforts of Baznas Jember in improving the status of mustahik to become muzakki in the village of SDGs Bangsalsari Jember, namely by providing business capital assistance, entrepreneurship training, mentoring and participating in promoting the products produced by mustahik. 3) The supporting and inhibiting factors for the distribution of ZIS in increasing the status of mustahik to become muzakki are, a) the following supporting factors, sufficient field human resources, the existence of business capital assistance funds and entrepreneurship training; b) while the inhibiting factors are the distribution of ZIS that is not right on target, weak control/assistance and the Covid-19 pandemic.